2018
DOI: 10.1007/s10519-017-9886-7
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Toddlerhood Self-Control and Later Externalizing Problems

Abstract: Lower self-control is a significant correlate or predictor of a wide range of adult outcomes, and this association may be due to more general tendencies toward childhood externalizing problems. The present study examined the association between toddlerhood self-control expressed within a "don't" compliance task (at 14-36 months) and later externalizing problems (parent-reported externalizing problems from age 4 to 12 years, teacher-reported externalizing problems from age 7 to 12 years, and self-reported condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 31 publications
(48 reference statements)
4
12
3
Order By: Relevance
“…Importantly, the current study demonstrates that when HH—a delinquent personality factor—is accounted for, impulsivity continues to share a bidirectional relationship with aggression among children and youth. Thus, despite recent research suggesting impulsivity is not a sufficient predictor of aggression when controlling for selfish tendencies (e.g., Rhee et al, ), this finding provides evidence to the contrary in a large sample.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…Importantly, the current study demonstrates that when HH—a delinquent personality factor—is accounted for, impulsivity continues to share a bidirectional relationship with aggression among children and youth. Thus, despite recent research suggesting impulsivity is not a sufficient predictor of aggression when controlling for selfish tendencies (e.g., Rhee et al, ), this finding provides evidence to the contrary in a large sample.…”
Section: Discussioncontrasting
confidence: 95%
“…Impulsivity; however, moderated the relationship between neglectful parenting at age 2 and greater aggression at age 12, 15, and 22, such that these relationships existed only in children who were high on impulsivity at a young age. Similar research from Rhee et al () examined impulsivity in toddlers and externalizing problems in childhood and adolescence. In this study, impulsivity was not associated with a parent or self‐reported aggressive behavior but was negatively associated with teacher‐report.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Different methodologies are available in the study of deviant (externalizing) and internalizing behavioral patterns in children and adolescents [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] . Most often standardized or structured questionnaires tailored to suit particular (the studied) demographics are used [11] , [12] , [13] , [14] , [15] . Evolving trends and behavioral patterns are often observed and made available as scientific findings.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%